Mycobacterium tuberculosis impairs dendritic cell response by altering CD1b, DC-SIGN and MR profile - Balboa, Luciana (2010)
During a chronic infection such as tuberculosis, the pool of tissue dendritic cells (DC) must be renewed by recruitment of both circulating DC progenitors and monocytes (Mo). However, the microenvironment of the inflammatory site affects Mo differentiation. As DC are critical for initiating a Mycobacterium tuberculosis-specific T-cell response, we argue that interference of M. tuberculosis with a correct DC generation would signify a mechanism of immune evasion. In this study, we showed thatearly interaction of c-irradiated M. tuberculosis with Mo subverts DC differentiation in vitro. We found that irradiated M. tuberculosis effect involves (1) the loss of a significant fraction of monocyte population and (2) an altered differentiation process of the surviving monocyte subpopulation. Moreover, in the absence of irradiated M. tuberculosis, DC consist in a major DC-specific intercellular adhesion molecule 3-grabbing non-integrin receptor (DC-SIGNhigh)/CD86low and minor DCSIGNlow/CD86high subpopulations, whereas in the presence of bacteria, there is an enrichment of DC-SIGNlow/CD86high population. Besides, this population enlarged by irradiated M. tuberculosis, which is characterized by a reduced CD1b expression, correlates with a reduced induction of specific T-lymphocyte proliferation. The loss of CD1molecules partially involves toll-like receptors (TLR-2)/p38 MAPK activation. Finally, several features of Mo, which have been differentiated into DC in the presence of irradiated M. tuberculosis, resemble the features of DC obtained from patients with active tuberculosis. In conclusion, we suggest that M. tuberculosis escapes from acquired immune response in tuberculosis may be caused by an altered differentiation into DC leading to a poor M. tuberculosis-specific T-cell response.